The Effect of Share Ownership Concentration and Company Operation Complexity towards Transfer Pricing Decisions - Siska Liana; Sugiono Poulus; Arie Pratama (Journal of Accounting Auditing and Business, 2020)
This research aims to examine the effect of share ownership concentration and company operation complexity on transfer pricing decisions. The transfer pricing decision in this research is measured by the total indicators of related party transactions of the company. The population in this research are all companies listed on the Indonesia Stock Exchange from 2017 to 2018. The sample selection technique used is purposive sampling and hence, 116 companies have been obtained. The data used in this research were obtained from financial statement data. The data analysis method used in the research is the multiple linear regression analysis. The results showed that share ownership concentration did not affect transfer pricing decisions, whereas company operation complexity projected by multinationality had a significant positive effect on transfer pricing decisions. Research shows that multinational companies are considered to have more significant opportunities by taking advantage of the differences in tax rates.